Comparative computational study of mechanical behavior in self-expanding femoropopliteal stents - Kareem, AK; Fakhri, OM; Ismail, Al Emran; Taib, I; Ali, IR; Nemah, MN (Penerbit UTHM, 2020)
The use of the stent to treat peripheral artery disease (PAD) is increased and the proportion of failures also increases. The femoropopliteal artery (FPA) experiences a high deformation ratio compared to the cardiovascular artery due to limp flexion and daily activities that could lead to stent failure, as well as increasing the number of observed mortality and morbidity. In the present work, two of the common PAD stent design models represented as STENT I and STENT II were analyzed by using of finite element method (FEM) to simulate the most mechanical loading modes that could occur in FPA, such as axial tension and compression, torsion, three-point bending and radial compression to give a good understanding of deformation that affected stent inside the in-vivo. The gradual force load was used to simulate all modes, the force values are 0.25 N, 0.5 N, 1.5 N, 2.5 N, 3.5 N and 5.5 N until the stent models obtain the yield-point. The comparison of stent models (STENT I, STENT II) was performed in terms of graphs of total deformation, force-stress and stress-strain for all test modes. The similarity ratio of the total deformation in axial tension and the compression mode for STENT I and STENT II was 17% and that may indicate that STENT I obtained a high deformation value instead of STENT II, while, the torsion similarity ratio was 86% which could show a good agreement in this mode, as well as the similarity ratio, was 78% of the total three-point bending deformation and the value of the similarity ratio in the radial compression mode was 23%. Still unclear what is the clinical mode of mechanical deformation that is more important than others with changing the length of the lesion and stent diameter, and the fatigue life test provides a better understanding of the mechanical tests that must be sought.